Unilateral imagined movement increases interhemispheric inhibition from the contralateral to ipsilateral motor cortex - Liang, Nan; Funase, Kozo; Takahashi, Makoto; Matsukawa, Kanji; Kasai, Tatsuya (Experimental brain research, 2014)
Whether a cortical drive to one limb modulates interhemispheric inhibition (IHI) from the active targeting to the non-active motor cortex (M1) remained unclear. The present study using a conditioning-test transcranial magnetic stimulation (TMS) paradigm aimed to directly demonstrate the modulation of IHI during unilateral voluntary or imagined movement in humans. Subjects were asked to actually perform right index-finger abduction (10–70 % of the maximum voluntary contraction) or to imagine the movement. Conditioning and test TMS with an interstimulus interval of 5, 10, and 15 ms were applied over the left and right M1, respectively, and the test motor evoked potential (MEP) was recorded from the left first dorsal interosseous (FDI) muscle. The conditioning TMS intensity was adjusted ranging from 0.6 to 1.4 (in 0.2 steps) times the resting motor threshold (rMT). With test TMS alone, MEP in the left FDI muscle significantly increased during voluntary or imagined movement of the right index-finger. MEP amplitude was significantly reduced in proportion to increments of the conditioning TMS intensity at rest (1.2 and 1.4 times the rMT, P < 0.05, respectively). Importantly, the MEP inhibition was markedly enhanced during voluntary or imagined movement in comparison with that at rest. The regression analysis revealed that IHI varied depending on the intensity of the impulses conveyed from left to right M1, but not on the corticospinal excitability of the active right hand. Our results suggest that IHI from the active to non-active M1 is enhanced during unilateral volitional motor activity.